Style and creativity: towards a theory of creative stylistics - Yoshifumi, Saitō (1997)
The purpose of this thesis is to present a new theory of creative stylistics as an antithesis to traditional description-oriented stylistics. For this purpose it undertakes: (1) a selective historical survey of stylistics with special attention to its academic formation in the context of the theoretical dissociation between linguistics and literary criticism (Chapter 1), (2) a theoretical survey of stylistics with special attention to the way it has been defined and subcategorized (Chapter 2), (3) a rearrangement of various stylistic theories according to the criterion of purpose, and a cognitively oriented demonstration of redefined linguistic, literary, and pedagogical stylistics (Chapter 3), (4) a theorization of creative stylistics as a prescriptively oriented discipline complementing the descriptivism of traditional stylistics, in terms of the cognitive processes of textual creation (Chapter 4), and (5) a demonstration of creative stylistics through an examination of my own literary writing, together with a discussion of further pedagogical and cross-cultural issues arising from this (Chapter 5).